Indexing and the performance-flow relation of actively managed mutual funds - Simon Lesmeister; Peter Limbach; P. Raghavendra Rau; Florian Sonnenburg (University of Cologne, Centre for Financial Research (CFR), 2022)
We exploit the staggered introduction of index funds in different segments and countries to study how increased competition from indexing affects the performance-flow relation and incentives of actively managed equity mutual funds. An increase in the market shares of available country-level index funds in active fund benchmarks is associated with a significantly lower sensitivity of flows to past performance and with a shift from a convex performance-flow relation towards a more linear relation. The increased competition from index funds is also associated with a higher fund performance-liquidation sensitivity, suggesting real economic consequences for active fund managers and fund management companies.
Keywords: G11; G23; G41; 330; performance-flow relation; performance-liquidation sensitivity; mutual funds; active management; passive management; competition